Biocatalytic conversion of microalgal biomass to biodiesel: optimization of growth conditions and synthesis of CaO bionanocatalyst from Monoraphidium sp. NCIM 5585 - Supriya Pandey; Thivaharan Varadavenkatesan; Raja Selvaraj; Ramesh Vinayagam (Scientific Reports)
Abstract Microalgal feedstock is a potential source for biodiesel production that addresses the challenges of fuel security and sustainable agriculture. This study aims to maximize biomass yield and lipid accumulation for freshwater microalga Monoraphidium sp. NCIM 5585 and utilize it for biodiesel production, contributing to the development of biocatalysis-based biofuels. Independent optimization studies were conducted to investigate critical growth parameters, viz., light intensity, photoperiod, and NaNO3 concentration. The study showed highest biomass productivity of 51.75 ± 1.9 mg/L.d and lipid content of 47.3 ± 0.02% (w/w) at 40 µmol/m2/s light intensity, 16 h L:08 h D photoperiod, and 0.25 g/L NaNO3. Further, a novel CaO bionanocatalyst was synthesized using residual microalgal biomass and characterized using SEM, EDX, FT-IR, and XRD. The characterization results from SEM and EDX confirmed the structural and elemental composition of bionanocatalyst with Ca and O as main elements. XRD revealed the crystalline nature of CaO with particle size of 17.83 nm. 86.5 ± 0.65% (w/w) FAME was obtained using the synthesized catalyst and was characterized using 1H NMR, 13C NMR and GC-MS. This study demonstrates the potential of Monoraphidium sp., optimized growth conditions and the significance of reusability of residual microalgal biomass as catalyst for sustainable biodiesel production, offering a promising solution for fuel security and biotechnology applications.